Methodology for the development of identification criteria of stone fruit brandy - L. N. Krikunova; S. M. Tomgorova; V. A. Zaharova (Пищевые системы)
The need to develop identification criteria for fruit brandy is connected with the prevention of the sale of counterfeit products on the Russian alcohol market. Due to the variety of factors affecting the final product, the solution to this problem requires the use of a methodology based on an integrated approach. The work is devoted to its first stage — the assessment of the influence of the biochemical composition of fruit stone raw materials, as well as various technological factors on the formation of essential (identification) characteristics of products. Fresh fruits of apricots, cherry plums, cherries, dogwood and plums, as well as samples of fermented raw materials were used as objects of research. The biochemical composition of fresh fruits was assessed by the content of sugars, free organic acids, amino acids and pectin substances. It has been found that the values of all main indicators of the biochemical composition varied widely in the samples of initial raw materials. At the same time, significant differences were noted between the types of fruit raw materials in the content of free amino acids (dogwood, cherry plum up to 0.08% and 0.12%, respectively; cherry, plum and apricot up to 0.19–0.30%) and pectin substances (cherry, apricot up to 0.6–0.8%; cherry plum, dogwood, plum up to 1.2–1.3%). The following factors were studied in the work as technological factors: a method of primary processing of raw materials (obtaining pulp or juice extraction); a maceration method — without enzyme preparations and with treatment with enzyme preparations; a fermentation method — without fermentation activators and using fermentation activators. It has been established that the method for primary processing of raw materials affects the concentration of methanol, esters and higher alcohols in fermented raw materials. The use of fermentation activators contributes to an increase in the concentration of higher alcohols and esters in them by almost 2 times, and the use of individual complex enzyme preparations — by 16% and 80%, respectively. It has been shown that the methodology for developing identification criteria for fruit vodkas at the first stage should include an assessment of the physico-chemical composition of initial raw materials and individual technological factors at the stage of preparing them for distillation.